PENERAPAN METODE QUANTUM TAHFIZ DALAM MENINGKATKAN HAFALAN AL-QUR’AN SANTRIWATI - Nuraini Nuraini; Alimron Alimron; Ahmad Syarifuddin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2022)
The purpose of this study is to determine the memorization of the Qur'an of female santri before the application of the Quantum Tahfiz method, 2. To determine the memorization of the Qur'an of female santri after the application of the Quantum Tahfiz method, 3. To determine the increase in memorization of the Qur'an of female santri before and after the application of the Quantum Tahfiz method. This type of research is quantitative and the research method used is the One-Group Pretest-Posttest experiment, the population in this study is 150 female students with a sample of 15 female students, data collection techniques using observation, tests, and documentation. Data analysis using the